Manajemen Sarana Prasarana Sekolah Berorientasi Adiwiyata Di SMA Negeri 2 Blora - Soeprijono, Gatot; , Prof. Dr. Bambang Sumardjoko; , Dr. Ahmad Muhibbin, M.Si (2017)
The purpose of this study was to describe how the procurement, use and maintenance of school infrastructure oriented Adiwiyata in SMA N 2 Blora. These include facilities and infrastructure; plots cleanliness for all citizens of the school, cleaning tools and means of supporting the preservation of the environment consisting of wheelie bins, waste banks, house garbage, tool biopori, herb, green house and a school cafeteria. The research is a qualitative empirically as it aims to describe an object, and using design tentative design. This study took place in SMA N 2 Blora. Sources of data in this study is the principal, vice principals areas of the curriculum, some teachers and students. Data collection techniques with interviews, observation and documentation. Data analysis technique used is a flow models of analisys through three stages: data reduction, data presentation and verification of data that take place simultaneously. To get the validity of the data, further data sources that there are triangulated to establish justification kohern continuous basis. The result showed that the procurement, use and maintenance of school infrastructure is the responsibility of all people in schools in coordination with the principal and deputy principal parts of infrastructure. At SMA N 2 Blora as Adiwiyata oriented schools, school facilities and infrastructure that supports Adiwiyata procurement by creating its own funds originating from the school and help others. The use of school infrastructure in SMA N 2 Blora in addition to regular activities on Friday 06.30 pm until 7:15 pm on Friday GAUL is known as the Movement of Action for the Environment, was also carried out if there are certain moments. In the event Friday Gaul, homeroom very important role in regulating its students to clean up and organize the school environment. Maintenance of infrastructure is also held at the event Friday Gaul and if something is broken or there is a need to be replaced, then held a repair or new purchase